Auditing Quality in China - Ding, Shengyan (2012)
In the research area of Chinese auditing market, few studies have been conducted on the effects that auditor-related characteristics have on auditing quality. Thus, the paper is to examine the influences auditor-related attributes have on auditing quality, including size of the auditing firm, its income, and whether it is Big 4 or not. In addition to that, research topic on relationship between relationship between market concentration level and auditing quality is also an attractive one among the researchers. However, many studies on this subject is usually performed on a short-run periods and many suggest with a dominative market structure. Thus this paper wants to broaden the time period of data to have a larger sample base and thus to test the relationship between market concentration and auditing quality to see whether the government should promote dominative market structure or not. Therefore, this paper mainly investigates two subjects in the Chinese auditing market: 1) auditor-related attributes’ impact on auditing quality; 2) market concentration level and its impact on auditing quality.